2021
DOI: 10.1002/oby.23245
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, inflammatory and thrombotic markers, and major clinical outcomes in critically ill patients with COVID‐19 in the US

Abstract: Objective This study aimed to determine whether obesity is independently associated with major adverse clinical outcomes and inflammatory and thrombotic markers in critically ill patients with COVID‐19. Methods The primary outcome was in‐hospital mortality in adults with COVID‐19 admitted to intensive care units across the US. Secondary outcomes were acute respiratory distress syndrome (ARDS), acute kidney injury requiring renal replacement therapy (AKI‐RRT), thrombotic events, and seven blood markers of infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Moreover, in patients admitted to the ICU an increased BMI has previously been described to be an independent risk factor for developing AKI (69,70). A finding which more recently has also been reported in patients with COVID-19 (71). This retrospective study has several strengths and limitations.…”
Section: Length Of Hospital and Icu Stay And Days On Mechanical Ventilationmentioning
confidence: 87%
“…Moreover, in patients admitted to the ICU an increased BMI has previously been described to be an independent risk factor for developing AKI (69,70). A finding which more recently has also been reported in patients with COVID-19 (71). This retrospective study has several strengths and limitations.…”
Section: Length Of Hospital and Icu Stay And Days On Mechanical Ventilationmentioning
confidence: 87%
“…Few studies measured the association between obesity and hospital mortality in this patient population, and among those who did, most included both critically ill and hospitalized patients with a less severe form of the disease [11,[20][21][22]. Among studies that focused on critically-ill patients, a significant harmful association between obesity and hospital mortality has not been observed consistently [18,[23][24][25][26][27][28][29]. A recent systematic review of predictors of in-hospital mortality in COVID-19 concluded that obesity was only associated with mortality in studies that included fewer critically-ill patients [24].…”
Section: Introductionmentioning
confidence: 99%
“…RESULTS: We included 94 patients. Median [q1, q3] body mass index (BMI) was 29 [26][27][28][29][30][31][32] kg/m 2 and 37% of patients were obese (defined as BMI > 30 kg/m 2 ). Hospital mortality for the entire cohort was 33%.…”
mentioning
confidence: 99%
“…Elevated serum cytokine levels, particularly IL-6 and TNFa, were observed in obese subjects (59,60). The obesity patients with increased BMI had abnormal circulation of inflammatory cytokines and are strongly associated in developing severe respiratory failure in COVID-19 (61,62). Leptin is a cytokine belonging to the family of proinflammatory cytokines and structurally similar to IL-6.…”
Section: Details Of Top 10 Melatonin Targets In Treating Obesitymentioning
confidence: 99%